Degradation of Amoxicillin by Bacterial Consortium in a Submerged Biological Aerated Filter: Volumetric Removal Modeling - Mohammad Ali Baghapour; Mohammad Reza Shirdarreh; Mohammad Faramarzian (Shiraz University of Medical Sciences, 2014)
Background: Amoxicillin is widely used as an antibiotic in the modern medicine. Due to its chemical structure, polarity, activity level, antibiotic specifications, and environmental sustainability, Amoxicillin leaks into the groundwater, surface waters, and drinking water wells. Many physical and chemical methods have been suggested for removing Amoxicillin from aquatic environments. However, these methods are so costly and have many performance problems. Methods: In this study, biodegradation of Amoxicillin by submerged biological aerated filter (SBAF) was evaluated in the aquatic environment. In order to assess the removal of Amoxicillin from the aquatic environment, this bioreactor was fed with synthetic wastewater based on sucrose and Amoxicillin at 3 concentration levels and 4 hydraulic retention times (HRTs). Results: The maximum efficiency for Amoxicillin and Soluble Chemical Oxygen Demand (SCOD) removal was 50.8% and 45.3%, respectively. The study findings showed that Stover- Kincannon model had very good fitness in loading Amoxicillin in the biofilter (R2 > 9 9%). T here w as n o a ccumulation o f Amoxicillin in the biofilm and the loss of Amoxicillin in the control reactor was negligible. This shows that removal of Amoxicillin from the system was due to biodegradation. Conclusions: It can be concluded that there was no significant inhibition effect on mixed aerobic microbial consortia. It was also observed that Amoxicillin degradation was dependent on the amount of Amoxicillin in the influent and by increasing the initial Amoxicillin concentration, Amoxicillin biodegradation increased, as well.